A SYSTEMATIC LITERATURE REVIEW ON RIDESHARING: DETERMINANTS, THEORETICAL GROUNDS AND METHODOLOGIES - Maryum Zaigham; Jakaria Dasan; Christie Pei-Yee Chin (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Ridesharing offers great benefits to its users. Although ridesharing literature has gained attention from researchers around the globe, the status quo of ridesharing literature especially among the riders and drivers still remains unclear. This literature review assesses recent ridesharing research to find out the regularity concerning determinants of ridesharing usage among riders and drivers. This review also explores the most preferred theoretical trends by ridesharing researchers as well as methodologies applied. Results show that customer satisfaction, service quality and trust were the most significantly researched factors in both the research streams. This review also portrays a steady progression of technology acceptance models up till the introduction of Technology Acceptance Model (TAM) and reveals quantitative mode as the most common mode of research. Finally, this analysis presents notable recommendations for upcoming ridesharing researchers.